2016
DOI: 10.25120/etropic.14.1.2015.3364
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the Dominant Discourses of Explicit Instruction and Culturally Responsive Pedagogy in the Far North Queensland Context:A Teacher’s Journey

Abstract: This study took place on a remote Torres Strait (TS) island in Far North Queensland (FNQ). It focused on my teaching journey in a grade 6/7 classroom. Through an Action Research (AR) methodology the study documents my efforts to navigate and respond to two teaching models – Explicit Instruction (EI) and Culturally Responsive Pedagogy (CRP), both of which inform policy statements in the region. As well, this study highlights the tensions that arose as a result of navigating this space. Using a reflective journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Studies of small‐group classroom activities have found that early finishers may indeed go off‐task (Carless, 2002; D'Aietti, 2017), and Sasaki (1996) reports that, while English teachers in Japanese colleges would like early finishers to extend in‐class activities, their perception was they did not generally do so. However, what actually happens when students finish tasks early remains relatively under‐examined, and the concept of “early finishers” lacks empirical grounding in research.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of small‐group classroom activities have found that early finishers may indeed go off‐task (Carless, 2002; D'Aietti, 2017), and Sasaki (1996) reports that, while English teachers in Japanese colleges would like early finishers to extend in‐class activities, their perception was they did not generally do so. However, what actually happens when students finish tasks early remains relatively under‐examined, and the concept of “early finishers” lacks empirical grounding in research.…”
Section: Introductionmentioning
confidence: 99%